Costs of European Monetary Union: Evidence of monetary and fiscal policy effectiveness - Helene Schuberth; Gert Wehinger (European Regional Science Association (ERSA), 1998)
Costs of a monetary union are typically analysed in the context of the optimum currency area approach, looking at the likelihood of asymmetric real disturbances, the degree of real wage flexibility and of labour mobility. But it is also important to consider the leeway of monetary and fiscal policy to respond to country-specific real shocks prior to entering the monetary union. Applying a structural VAR model to Austria, Belgium, the Netherlands, Sweden, Finland, France, Italy and the United Kingdom indicates that costs of giving up autonomous monetary policy in a European Monetary Union (EMU) would generally not be too high. Only in Italy and the United Kingdom autonomous monetary policy has shown positive short-run output effects in the past, in all other countries such effects are negligible or not significant. Some cushioning influence of adverse EMU effects, then, could be expected from autonomous fiscal policy measures, since results suggest that, with the exception of Finland and again Italy and the United Kingdom, autonomous fiscal policy had positive short-run output effects in the past in all cases, those effects being somewhat more pronounced in Belgium and Sweden.
Keywords: 330